208k views
0 votes
Solve for x:

(3)/(x+y) -(3x-3y)/(2x-3y) *((2x-3y)/(x^2-y^2)-2x+3y)

1 Answer

5 votes

Answer:

x = -(3 y)/2

Explanation:

Solve for x:

-2 x - 3 y + 3/(x + y) - (3 x - 3 y)/(x^2 - y^2) = 0

Simplify and substitute z = x + y.

-2 x - 3 y + 3/(x + y) - (3 x - 3 y)/(x^2 - y^2) = -y - 2 (x + y)

= -y - 2 z:

-y - 2 z = 0

Multiply both sides by -1:

y + 2 z = 0

Subtract y from both sides:

2 z = -y

Divide both sides by 2:

z = -y/2

Substitute back for z = x + y:

x + y = -y/2

Subtract y from both sides:

Answer: x = -(3 y)/2


User Benito Serna
by
6.0k points